Classical world, female lyrics voice and expression of desire in the poetry of Aurora Luque (Minerva, 2019)
The objetive of this paper is to study some aspects of the Classical Tradition in Aurora Luque’s poetry. We will focus on the famous topics of tempus fugit and carpe diem and will also study the intertextuality of her poetry with Catullus’ poems. We will show how Luque breaks the male discourse about love and desire using them.
Keywords: Classical tradition; Aurora Luque; Greek and Latin topoi; desire; love; Catullus